Cost effective computerized decision support: tracking caregiver acceptance at the point of care. - Wallace, C. J. (American Medical Informatics Association, 1995)
We implemented a computerized decision support tool to standardize the administration of supplemental oxygen (O2) therapy in the acute care (non-ICU) hospital setting. Caregiver acceptance of the computerizeds oxygen therapy protocol (COTP) instructions was measured to determine the clinical performance of the computerized decision support tool. 49.6% of instructions generated were followed by the clinical caregiver, and 16.8% of instructions generated were explicitly acknowledged by the user through the COTP computer interface. Despite this low caregiver response rate, significant favorable changes in the administration of oxygen were observed. This paper is focused on the issues of general importance the caregiver response rate raises for the implementation and clinical use of computerized decision support tools, including: (1) limitations of the user interface and (2) inherent difficulty in changing long-standing practice patterns.